2002
DOI: 10.1037/0882-7974.17.3.416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on flashbulb memories.

Abstract: The authors investigated the effect of aging on flashbulb (FB) memories. In 1996, elderly Turks recalled how they had heard about 2 remote events--the death of the first president of Turkey (in 1938) and another event involving a change in the national borders of the country (in 1939)--and both elderly and younger adults recalled how they heard about the recent death of the 8th president of Turkey (in 1993). Seventy percent of the elderly had FB memories for the 1938 death; critical variables for the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
2
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 35 publications
8
53
2
4
Order By: Relevance
“…For the WWII population in Study 1, a similar pattern was observed for the presence and vividness of participants' personal memories of the day of the German invasion and the day of their capitulation, (though vividness also correlated weakly with age after age 7). The findings related to memories for the two historical events agree with studies of childhood amnesia generally (e.g., Nelson, 1993;Rubin, 2000;Pillemer & White, 1989;Usher & Neisser, 1993) and more specifically with previous studies on age differences in the development of flashbulb memories (Berntsen & Thomsen, 2005;Teckan & Pernircio lu, 2002;Winograd & Killinger, 1983). The fact that the relation between longterm posttraumatic stress reactions and age at the time of the event mirrors the age-related ability of retaining autobiographical memories from childhood to adulthood has at least two possible interpretations: One possibility is that posttraumatic stress reactions (in terms of reexperiencing, avoidance and hyperarousal, American Psychiatric Association, 1994) depend on the presence of autobiographical memory abilities.…”
Section: Discussionsupporting
confidence: 90%
“…For the WWII population in Study 1, a similar pattern was observed for the presence and vividness of participants' personal memories of the day of the German invasion and the day of their capitulation, (though vividness also correlated weakly with age after age 7). The findings related to memories for the two historical events agree with studies of childhood amnesia generally (e.g., Nelson, 1993;Rubin, 2000;Pillemer & White, 1989;Usher & Neisser, 1993) and more specifically with previous studies on age differences in the development of flashbulb memories (Berntsen & Thomsen, 2005;Teckan & Pernircio lu, 2002;Winograd & Killinger, 1983). The fact that the relation between longterm posttraumatic stress reactions and age at the time of the event mirrors the age-related ability of retaining autobiographical memories from childhood to adulthood has at least two possible interpretations: One possibility is that posttraumatic stress reactions (in terms of reexperiencing, avoidance and hyperarousal, American Psychiatric Association, 1994) depend on the presence of autobiographical memory abilities.…”
Section: Discussionsupporting
confidence: 90%
“…On the one hand, our recent studies of flashbulb memory (FM), which require people to recollect where, when, or from whom they learned about an emotional event in the real world (e.g., the September 11th, 2001, terrorist attacks; Brown & Kulik, 1977) have shown no differences between young and older adults (Davidson, Cook, & Glisky, 2006;Davidson & Glisky, 2002; see also Otani et al, 2005;Wright, Gaskell, & O'Muircheartaigh, 1998; but see Cohen, Conway, &Maylor, 1994, andTekcan &Peynircioǧlu, 2002, for conflicting findings). We speculated that the emotional arousal associated with FMs may have enhanced the processes important for the encoding of source information, eliminating the age-related deficit usually found in laboratory studies of source memory.…”
Section: Aging and Item And Source Memorymentioning
confidence: 99%
“…Following Kvavilashvili et al (2003) and Tekcan and Peynircioglu (2002), we used a 3-point scoring system (from "0" to "2") to code the specificity of participants" answers to canonical questions about time, location, activity, source and others present. A score of '2' was assigned when the response contained specific information, for example, a particular radio station (Capital FM) in response to a question about the source.…”
Section: Effects Of Age On Flashbulb and Non-flashbulb Memories 14mentioning
confidence: 99%
“…To assess whether flashbulb memories are similar to usual cases of source memory it may be necessary to examine age effects with longer delay intervals (cf. Tekcan & Peynircioglu, 2002). To address these issues, the current study examined flashbulb memories of September 11 (possibly the most tragic event in flashbulb research so far), used a long delay of almost two years and thoroughly assessed the cognitive status of participants.…”
mentioning
confidence: 99%